The big bang theory. The complete eleventh season [videorecording (DVD)] - Cendrowski, Mark; Lorre, Nikki; Galecki, Johnny; Parsons, Jim, 1973-; Cuoco, Kaley (Warner Bros. Entertainment, 2018)
Two roommates, both genius physicists, live in their own world with their friends until an attractive woman moves in across the hall and helps them see life in different ways.